Stres akademik pada mahasiswa Merdeka Belajar Kampus Merdeka (MBKM): Bagaimana peran dukungan sosial? - Vian, Alvian Rizky Saputra; Andik Matulessy; Suhadianto (INNER: Journal of Psychological Research, 2023)
Abstract The MBKM program has a big impact on the connection between universities and the industrial world, however, on the other hand, the MBKM program which was implemented suddenly caused several students to experience academic stress. This research aims to explore the relationship between social support and academic stress in students taking part in the Merdeka Belajar Kampus Merdeka (MBKM) program. The research participants were 85 students who were recruited using convenience sampling techniques. Data collection uses academic stress and social support scales which have been declared valid and reliable through psychometric testing. The results of hypothesis testing using Product Moment Correlation show that there is a significant negative relationship between social support and academic stress in students taking part in the MBKM program. Implications for future research will be discussed. Keywords: Social Support, MBKM Students, Merdeka Learning Independent Campus, Academic Stress.